BS EN 16272-6. Railway applications. Infrastructure. Noise barriers and related devices acting on airborne sound propagation. Test method for determining the acoustic performance. Part 6. Intrinsic characteristics. In situ values of airborne sound insulation under direct sound field conditions (17th February 2022) - British Standards Institution,
No abstract available